Analysis of Shopping Cart in Retail Companies Using Apriori Algorithm Method and Model Profset - putri agung permatasari (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
This research needed a priori algorithm method to produce association rules, with a